Respuesta :

1)

[tex] \dfrac{3}{4} + 5 - \dfrac{1}{2} = \dfrac{3}{4} + \dfrac{20}{4} - \dfrac{2}{4} = \dfrac{21}{4} = 5 \dfrac{1}{4} [/tex]

2)

[tex] \dfrac{2}{3} + {2}^{3} - \dfrac{1}{3} = \dfrac{2}{3} + \dfrac{24}{3} - \dfrac{1}{3} = \dfrac{25}{3} = 8 \dfrac{1}{3} [/tex]

3)

[tex] - 15 + 6x - 19 - 20x = - 14x - 34[/tex]

4)

[tex] - 7x - 2 - 9y + 10x = 3x - 9y - 2[/tex]

5)

[tex]14 + x = 18 \\ x = 18 - 14 \\ x = 4[/tex]

6)

[tex] - 5x = - 15 \\ x = - 15 \div ( - 5) \\ x = 3[/tex]

7)

[tex] - 2x + 8 = 18 \\ - 2x = 18 - 8 \\ - 2x = 10 \\ x = 10 \div ( - 2) \\ x = - 5[/tex]

8)

[tex]3x + 18 - 8x = - 17 \\ 3x - 8x = - 17 - 18 \\ - 5x = - 35 \\ x = - 35 \div ( - 5) \\ x = 7[/tex]

ACCESS MORE